Impact of a sudden drop in ambient temperature on some phenotypic and functional properties of the camel’s immune system (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: There is a particular lack of studies on the immune response of camels to cold stress conditions. The present study aimed, therefore, at the ex vivo investigation of the effect of a sudden decline in ambient temperature on some phenotypic and functional immunological parameters in camels. Materials and Methods: Using flow cytometry and antibody staining, leukocyte composition, distribution of lymphocyte subsets, and the expression of some cell activation markers were analyzed in camels under normal temperatures and a few days following a sudden environmental temperature decrease. In addition, phagocytosis activity and capacity of neutrophils and monocytes incubated ex vivo with Zymosan A Bioparticles or Staphylococcus aureus were comparatively investigated before and after cold exposure of the camels. Results: Exposure of the camels to low ambient temperatures resulted in a significant increase in the total white blood cell count and the absolute counts of neutrophils and lymphocytes. On the other hand, the decrease in monocyte counts after cold exposure resulted in a decreased lymphocyte-to-monocyte ratio. In addition, ex vivo analysis of phagocytosis and activation marker expression revealed reduced phagocytosis activity and capacity, as well as the downregulation of the activation markers CD44 and lymphocyte function-associated antigen 1 on leukocytes from the camels after cold exposure. Conclusion: The current study identified a significant impact of exposure to low ambient temperatures on the distribution of leukocyte subpopulations in camel blood. In addition, ex vivo analysis of phagocytosis revealed the impaired innate antimicrobial function of phagocytes in camels under cold stress. The underlying mechanisms for the observed effects of cold stress on the camel’s immune system and their clinical significance for camel health remain to be elucidated in further studies.J. Adv. Vet. Anim. Res., 12(3): 929–940, September 2025http://doi.org/10.5455/javar.2025.l954